2020
DOI: 10.33860/jbc.v1i2.123
|View full text |Cite
|
Sign up to set email alerts
|

Kombinasi Metode Pijat Woolwich dan Massage Rolling (Punggung) Memengaruhi Kecukupan ASI pada Ibu Post Partum

Abstract: One of the failures of exclusive breastfeeding is the lack of a mother's level of confidence that her mother's milk cannot fulfill her baby's nutritional needs. Efforts that can be made to stimulate the hormone prolactin and oxytocin in the mother after childbirth is to provide a relaxed sensation in the mother by doing Woolwich massage and rolling massage (back). The purpose of this study was to determine the effect of a combination of Woolwich massage methods and Rolling Massage on Adequacy in postpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
1
0
4
Order By: Relevance
“…Usman Research (2019) performed a combination of Woolwich massage method and rolling massage . The combination of these methods is done at the time of home visits so that it can increase family participation in efforts to enhance breast milk (Usman 2019). Results of research Albertina (2015) found there is a significant relationship between lactation massage and smooth milk production in mothers post sectiocaesarea day 2-3 (Meity Albertina, Hj.…”
Section: Smooth Milk Production During the Postpartum Period (0-7 Days)mentioning
confidence: 99%
“…Usman Research (2019) performed a combination of Woolwich massage method and rolling massage . The combination of these methods is done at the time of home visits so that it can increase family participation in efforts to enhance breast milk (Usman 2019). Results of research Albertina (2015) found there is a significant relationship between lactation massage and smooth milk production in mothers post sectiocaesarea day 2-3 (Meity Albertina, Hj.…”
Section: Smooth Milk Production During the Postpartum Period (0-7 Days)mentioning
confidence: 99%
“…Pertumbuhan dan perkembangan bayi sebagian besar ditentukan oleh jumlah ASI yang diperoleh termasuk energi dan zat gizi lainnya yang terkandung di dalam ASI tersebut (Usman, 2019) (Sumiatik, 2022). Maka dari itu ibu hamil harus mampu mengelolah stress selama kehamilan, menyusui, dan perawatan payudara sehingga proses pengeluaran ASI lancar (Wahyuni & Noviyanti, 2019).…”
Section: Pendahuluanunclassified
“…Area ini merupakan area dimana wanita sering mengalami ketegangan otot bagi ibu postpartum. Memijat punggung dapat merilekskan bahu dan merangsang refleks letdown (Usman, 2019).…”
Section: Hasil Dan Pembahasanunclassified